The British Monopolies Commission - Rowley, Charles Kershaw (London: Allen & Unwin, 1966)
The book combines a detailed critical study of the Monopolies Commission itself, with an analysis of the economic issues involved in monopoly supervision and control.
Includes bibliographical references and index
lje 14/06/2017
Loans
Keywords: Monopolies; United Kingdom